Analisis Komparatif Kinerja Keuangan pada Bank Pembangunan Daerah di Wilayah Kalimantan Selama dan Setelah Pandemi COVID-19 - Olga, Olga (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2026)
This study aims to examine differences in the financial performance of Regional Development Banks in the Kalimantan region during and after the COVID-19 pandemic. The study compares the financial performance of Bank Kalbar, Bank Kalteng, Bank Kalsel, and Bank Kaltimtara using financial ratios consisting of Loan to Deposit Ratio, Capital Adequacy Ratio, Non Performing Loan, Net Interest Margin, Return on Assets, Return on Equity, and Operating Expenses to Operating Income. This research employs a quantitative comparative approach using secondary data obtained from the annual financial reports of the Regional Development Banks during the 2020–2023 period. The data cover two years during the COVID-19 pandemic and two years after the pandemic. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and paired sample t-tests with SPSS version 25. The results show that there are no significant differences in Loan to Deposit Ratio, Non Performing Loan, Net Interest Margin, Return on Assets, Return on Equity, and Operating Expenses to Operating Income during and after the COVID-19 pandemic. However, there is a significant difference in Capital Adequacy Ratio. These findings indicate that the financial performance of Regional Development Banks in Kalimantan was relatively stable after the pandemic, with the most notable change occurring in capital adequacy.